Music in the Works of Ignas Šeinius: A Few Chords - Ivanova, Giedrė (Colloquia, 2022)
In this article, the author focuses on the expression of music in the early texts of Lithuanian prose innovator Ignas Jurkūnas Šeinius (1889–1959). Starting with Werner Wolf’s typology of the relations between words and music, and incorporating insights from other scholars (Lars Elleström, Siglind Bruhn, Vytautas Kubilius, Irina Melnikova, etc.), the article discusses the different forms of music and the meanings they produce in Šeinius’ novel Kuprelis (1913, 1932), in one segment of his short story “Vasaros vaišės” [Summer Feast, 1914], and in the novella “Marių daina” [The Song of the Lagoon, 1914].The analysis has shown that in the novel Kuprelis, music expression explicates the experiences of the main characters, their self-perception and relationship to other characters, becoming a symbol of love, and pointing to and predicting important moments in the story. In the analyzed passage from the short story “Summer Feast,” one can notice a parallel with the musical form of fugue, which creates the impression of multiple motifs sounding and being perceived at the same time, and which emphasizes the aspect of the existential climax that is being developed by the narrative. Combining music, literature and painting, the novella “The Song of the Lagoon” echoes the synthesis of these arts captured in Mikalojus Konstantinas Čiurlionis’s pictorial sonata “Jūra” [The Sea].” The ekphrastic nature of the novella invites the reader to see the figures from the paintings reproduced using words, and to hear the musical motifs that accompany them.
Keywords: Ignas Šeinius; music; intermediality; music in literature; fugue; ekphrasis